Exploring the Two-Way Link between Migraines and Venous Thromboembolism: A Bidirectional Two-Sample Mendelian Randomization Study - Wang, Yang; Hu, Xiaofang; Wang, Xiaoqing; Li, Lili; Lou, Peng; Liu, Zhaoxuan (Thrombosis and Haemostasis, 2024)
Background The objective of this study is to utilize Mendelian randomization to scrutinize the mutual causality between migraine and venous thromboembolism (VTE) thereby addressing the heterogeneity and inconsistency that were observed in prior observational studies concerning the potential interrelation of the two conditions.Methods Employing a bidirectional Mendelian randomization approach, the study explored the link between migraine and VTE, incorporating participants of European descent from a large-scale meta-analysis. An inverse-variance weighted (IVW) regression model, with random-effects, leveraging single nucleotide polymorphisms (SNPs) as instrumental variables was utilized to endorse the mutual causality between migraine and VTE. SNP heterogeneity was evaluated using Cochran's Q-test and to account for multiple testing, correction was implemented using the intercept of the MR-Egger method, and a leave-one-out analysis.Results The IVW model unveiled a statistically considerable causal link between migraine and the development of VTE (odds ratio [OR] = 96.155, 95% confidence interval [CI]: 4.342–2129.458, p = 0.004), implying that migraine poses a strong risk factor for VTE development. Conversely, both IVW and simple model outcomes indicated that VTE poses as a weaker risk factor for migraine (IVW OR = 1.002, 95% CI: 1.000–1.004, p = 0.016). The MR-Egger regression analysis denoted absence of evidence for genetic pleiotropy among the SNPs while the durability of our Mendelian randomization results was vouched by the leave-one-out sensitivity analysis.Conclusion The findings of this Mendelian randomization assessment provide substantiation for a reciprocal causative association between migraine and VTE within the European population.
Keywords: Mendelian randomization; migraine; venous thromboembolism; bidirectional; causality